Case report: Guillain-Barré syndrome following acute ischemic brainstem stroke - Da Xu; Cheng Yu; Xue-Jun Deng; Man Li (Frontiers in Immunology)
Guillain–Barré syndrome (GBS) is a heterogeneous disease, and it usually develops after an antecedent infection, while rare cases develop following a central nervous system disease. Given the indeterminacy of prodromal infection symptoms and the overlap of symptoms with other neurological disorders, a rigorous clinical and neurological examination in conjunction with history is necessary for early diagnosis and treatment of GBS. Here we present a rare case of GBS following acute ischemic stroke which was different from previous reports such as GBS following hemorrhagic stroke or head trauma. Moreover, intravenous immunoglobulin was effective in this patient after 6 months of follow-up despite the potential risk of thrombotic events.